2019
DOI: 10.1016/j.bbmt.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Human Rhinovirus Infections in Hematopoietic Cell Transplant Recipients: Risk Score for Progression to Lower Respiratory Tract Infection

Abstract: A B S T R A C T Human rhinovirus lower respiratory tract infection (LRTI) is associated with mortality after hematopoietic cell transplantation (HCT); however, risk factors for LRTI are not well characterized. We sought to develop a risk score for progression to LRTI from upper respiratory tract infection (URTI) in HCT recipients. Risk factors for LRTI within 90 days were analyzed using Cox regression among HCT recipients with rhinovirus URTI between January 2009 and March 2016. The final multivariable model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 42 publications
4
32
0
Order By: Relevance
“…In view of the prolonged shedding, defining predictors of HRV lower RTID and mortality, such as grading SID or ISI, are warranted to guide decisions regarding transplant deferral and/or selective treatment of allogeneic HCT patients at highest risk ( 5 ). In a recent retrospective single-center study of 588 HRV upper RTID events in 150 autologous and 438 allogeneic HCT recipients, 16 and 84 were found to progress to lower RTID, respectively ( 182 ). Following multivariate analysis, a novel weighted risk score was derived consisting of a total of 99 points, which were given at upper RTID diagnosis, including for steroid use (20 for ≥2 mg/kg bodyweight; 12 for ≥1 to <2 mg/kg), 16 for lymphocyte counts of <100/μl, 14 for allogeneic/unrelated donor, and 12 for a positive CMV recipient status.…”
Section: Carv-specific Aspects In Transplant Patientsmentioning
confidence: 99%
“…In view of the prolonged shedding, defining predictors of HRV lower RTID and mortality, such as grading SID or ISI, are warranted to guide decisions regarding transplant deferral and/or selective treatment of allogeneic HCT patients at highest risk ( 5 ). In a recent retrospective single-center study of 588 HRV upper RTID events in 150 autologous and 438 allogeneic HCT recipients, 16 and 84 were found to progress to lower RTID, respectively ( 182 ). Following multivariate analysis, a novel weighted risk score was derived consisting of a total of 99 points, which were given at upper RTID diagnosis, including for steroid use (20 for ≥2 mg/kg bodyweight; 12 for ≥1 to <2 mg/kg), 16 for lymphocyte counts of <100/μl, 14 for allogeneic/unrelated donor, and 12 for a positive CMV recipient status.…”
Section: Carv-specific Aspects In Transplant Patientsmentioning
confidence: 99%
“…These definitions were also applied in studies on coronavirus, 32 parainfluenza virus 33 and rhinovirus. 34…”
Section: Incidence Of Respiratory Syncytial Virus Infectionmentioning
confidence: 99%
“…Several studies have looked at the effect on mortality of when CARV infection occurs after allo-HCT using heterogeneous cut-off time points, showing discrepant results [6,10,11,[14][15][16][17][18][19][20][21][22][23][24]. In fact, most of them were unable to find any association between timing and mortality [14][15][16][17][18][19][20][21][22]24]. In contrast, our detailed analysis of 3-month all-cause mortality conducted monthly during the first year revealed that most deaths occurred in recipients who developed a CARV infection within the first 6 months of transplant (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, some studies found that developing a CARV infection within 30 days after transplant was linked to worse outcome [6,10] whereas others did not [14][15][16][17][18]. In addition, studies using day + 100 as a cut-off time could not show significant association with outcome [19][20][21][22], while others observed worse outcome for CARV infections occurring before day + 180 [11]. Finally, while some studies found that CARVs beyond 1 year after allo-HCT showed favorable outcomes [23], others did not [14,17,24].…”
Section: Introductionmentioning
confidence: 99%